Motivasi Belajar Peserta Didik Pada Pembelajaran dalam Jaringan (Studi Kasus Kelas VII B SMP Plus Al-Ma'arif) - Fatimatuz Zahro; Moh. Saiful Bakhril Amin (JIECO: Journal of Islamic Education Counseling, 2021)
The purpose of this study is to find out how Distance Learning (PJJ) is using the network (online) so that it causes students to decrease in learning motivation. This study uses a qualitative research method using the center bunch dialogue/focus group discussion technique. The research subjects were conducted on 6 students of class VII B at SMP Plus Al-Ma'arif. The results of the study indicate that students feel that online learning is less understandable and places more emphasis on assignments than giving and explaining material, which makes it difficult to understand in learning and ultimately leads to lazy learning. This is what ultimately makes the motivation to learnless